Comparing the impact of personal and parental risk factors, and parental lifespan on all-cause mortality and cardiovascular disease: findings from the Midspan Family cohort study. Issue 10 (28th May 2015) - Hart, Carole; McCartney, Gerry; Gruer, Laurence; Watt, Graham
Abstract : Background: We aimed to identify which personal and parental factors best explained all-cause mortality and cardiovascular disease (CVD). Methods: In 1996, data were collected on 2338 adult offspring of the participants in the 1972–1976 Renfrew and Paisley prospective cohort study. Recorded risk factors were assigned to 5 groups: mid-life biological and behavioural (BB), mid-life socioeconomic, parental BB, early-life socioeconomic and parental lifespan. Participants were followed up for mortality and hospital admissions to the end of 2011. Cox proportional hazards models were used to analyse how well each group explained all-cause mortality or CVD. Akaike's Information Criterion (AIC), a measure of goodness-of-fit, identified the most important groups. Results: For all-cause mortality (1997 participants with complete data, 111 deaths), decreases in AIC from the null model (adjusting for age and sex) to models including mid-life BB, mid-life socioeconomic, parental BB, early-life socioeconomic and parental lifespan were 55.8, 21.6, 10.3, 7.3 and 5.9, respectively. For the CVD models (1736 participants, 276 with CVD), decreases were 37.8, 3.7, 6.7, 17.3 and 0.4. Mid-life BB factors were the most important for both all-cause mortality and CVD; mid-life socioeconomic factors were important for all-cause mortality, and early-life socioeconomic factors were important for CVD. Parental lifespan was the weakest factor. Conclusions: As mid-life BB risk factors best explained all-cause mortality and CVD, continued action to reduce these is warranted. Targeting adverse socioeconomic factors in mid-life and early life may contribute to reducing all-cause mortality and CVD risk, respectively.